PRINSIP DAN PRAKTIK PENDIDIKAN AGAMA KRISTEN DALAM KITAB EFESUS - Manik, Julkipri; Hutagalung, Tasya Ivana (STT Injili Indonesia Medan, 2022)
Education is a principle thing in human life, including spiritual education. In this case, Christian Religious Education becomes a need for Christians in all ages. The Bible is the basis for teaching Christian Religious Education for God's people. And in this discussion, the text chosen to be studied is the Book of Ephesians. Where there are educational principles and practices imparted to God's people. Indeed, this is inseparable from the principles and practices of spiritual education carried out by the Jews in Old Testament times. Ephesus itself is the right reference if we want to learn many things related to Christian religious education. Through the library research method, it is hoped that the objectives of this research can be achieved.Key word: Spiritual education, Christian, Ephesians